2001
DOI: 10.1016/s0735-1097(01)01419-x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and mortality of the Brugada-type electrocardiogram in one city in Japan

Abstract: A substantial number of the Brugada-type ECG were observed in subjects in a community-based population in Japan, especially in men. The total mortality of subjects with the Brugada-type ECG did not differ from the mortality of those without the Brugada-type ECG in a community-based population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
124
5
7

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 227 publications
(146 citation statements)
references
References 12 publications
10
124
5
7
Order By: Relevance
“…In contrast, Priori et al found no episodes of malignant arrhythmias over a period of 3 years in 30 asymptomatic patients with a Brugada sign 9 . A very low rate of arrhythmic events in this patient group has been confirmed by multiple recent and larger-scale studies 7,[10][11][12][13] . In one study of 14,000 individuals in Japan, the mortality rate of 98 subjects with a Brugada sign was not higher than the rest of the cohort 7 .…”
Section: Introductionsupporting
confidence: 69%
See 2 more Smart Citations
“…In contrast, Priori et al found no episodes of malignant arrhythmias over a period of 3 years in 30 asymptomatic patients with a Brugada sign 9 . A very low rate of arrhythmic events in this patient group has been confirmed by multiple recent and larger-scale studies 7,[10][11][12][13] . In one study of 14,000 individuals in Japan, the mortality rate of 98 subjects with a Brugada sign was not higher than the rest of the cohort 7 .…”
Section: Introductionsupporting
confidence: 69%
“…A very low rate of arrhythmic events in this patient group has been confirmed by multiple recent and larger-scale studies 7,[10][11][12][13] . In one study of 14,000 individuals in Japan, the mortality rate of 98 subjects with a Brugada sign was not higher than the rest of the cohort 7 . Despite the discrepancy in prognosis among different studies, there is evidence that some asymptomatic individuals with a Brugada-type ECG tend to die suddenly during sleep, a clinical observation characteristic of SUNDS, suggesting that SUNDS may underlie at least a part of Brugada-type ECG.…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…Although the prevalence of BS is higher in Asian countries, [28][29][30][31][32] the prevalence of Brugada-type ECGs in Japan is only 0.14-1.22%. [29][30][31][32] All patients in the present study were recruited from only 1 institute. Therefore, further prospective studies using a large number of patients are needed to validate the present findings.…”
Section: Study Limitationsmentioning
confidence: 95%
“…A type I Brugada ECG pattern is found rarely in the European population, but it appears more commonly in Southeast Asia, with an estimated prevalence of 0.12% in Japan. 9,10 No apparent structural heart disease can be found in BrS, at least macroscopically. Some microscopic myocardial alterations have been reported, suggesting that the channelopathy may induce cardiomyopathic changes in some patients.…”
Section: Clinical Diagnosis Diagnostic Criteriamentioning
confidence: 99%